Female Labor Market Transitions in Europe - Lutz C. Kaiser (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Using micro panel data, labor market transitions are analyzed for the EU-member states by cumulative year-by-year transition probabilities. As female (non-)employment patterns changed more dramatically than male employment in past decades, the analyses mainly refer to female labor supply. In search for important determinants of these transitions, six EUcountries with different labor market-regimes are selected as examples (Denmark, Germany, Netherlands, Portugal, Ireland, UK). Within these countries, women?s determinants of labor market transitions are compared by means of pooled multinominal logit-regressions. The outcomes hint at both, the importance of socio-economic determinants, like the life cycle or human capital, but also address gender related differences in the paths of labor market transitions. Clearly, the observed cross-national differences are driven by specific national institutional settings. Among others, one of the most crucial features is the day-care infrastructure concerning children, which either fosters or restricts a sustainable risk management between family and work in the respective countries.
Keywords: J78; J21; J22; 330; labor supply; labor market transitions; socio-economic determinants; institutional settings; risk management; cross-national comparison